PENGARUH MODEL PAKEM BERBASIS TIK PADA MATERI TRIGONOMETRI TERHADAP KEMANDIRIAN BELAJAR SISWA - Rohim, Mohammad Fatkur; Zahri, Mohammad (Jurnal Pembelajaran Matematika, 2018)
Abstract:Self-autonomous learning is an attitude of learning by taking an initiative, regulating and controlling learning, seeking and utilizing relevant learning resources, choosing and implementing learning strategies, and evaluating learning outcomes. Self-autonomous learning needs to be developed, because it is a thing that determines the success of Active, Creative, Effective, and Fun Learning implementation to achieve students? learning outcomes. This study aims to examine the effect of Active, Creative, Effective, and Enjoyable Learning Models (PAKEM) on students? self-autonomous learning at tenth grade in development design program of State Vocational School (SMKN) 3 Surabaya in the academic year of 2017/2018. This research is an experimental research. The population is tenth grade students of development Design of SMKN 3 Surabaya in the academic year of 2017/2018. The samples in this study are 15 students, consisting of 5 male students and 10 female students. The instrument used to collect data is self-autonomous learning questionnaire. The questionnaire trial includes content validity and reliability. The results show that there is a positive and significant influence on students? self-autonomous learning after the implementation of PAKEM model. It can be seen based on t test,  = 2.078 greater than  = 1.761 with a significance level of 0.05%. Thus the overall results of this analysis support the proposed hypothesis.Keywords:PAKEM, Self-autonomous Learning, Trigonometry.